Diffusion coefficients in ionic liquids: relationship to the viscosity. - Brookes, R; Davies, A; Ketwaroo, G; Madden, P (2005)
The relationship between the diffusion coefficient and the viscosity has been examined in computer simulations for a number of ions diffusing in a molten salt (alkali halide) solvent. The comparison gives a measure of a hydrodynamic radius for the diffusing ions which is then compared with the bare ionic radius and a characteristic radius of the coordination complex formed by halide ions around polyvalent cations. K(+) and Cl(-) ions appear to diffuse as isolated spherical particles, whereas the trivalent cations Sc(3+), Y(3+), and La(3+) diffuse as if with an intact coordination shell. These different behaviors can be related to the time scale for the relaxation of the coordination shell, compared to the structural relaxation time of the solvent.